CELL PHONE IMPACT ON USER HEALTH AND CELL PHONE USAGE HABITS AMONG ADULTS - Strode, Zanda; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of research is to find out mobile phone adult user habits and understanding of electromagnetic field effects on health. A comprehensive literature searches and analyzation was conducted in the electronic databases (Pubmed, Accessmedicine etc.), to find out later research outcomes about electromagnetic field impact on health, also electronic survey was conducted and results statisticaly  processed with SPSS 24. 192 respondents participated in study:  117– females, 75– males in age range from 18 to 55 years. Hypothesis: Understanding the electromagnetic field health effects reduce the use of mobile phones on a daily basis not confirmed, because the majority of respondents are not willing to change their cell phone use patterns, or believe that it is not possible.